Glassware design and drinking behaviours: a review of impact and mechanisms using a new typology of drinking behaviours. Issue 1 (2nd January 2022) - Langfield, Tess; Pechey, Rachel; Pilling, Mark A.; Marteau, Theresa M.
ABSTRACT: Much of the global burden of disease is attributable to unhealthy behaviour, including excessive consumption of alcohol and sugar-sweetened beverages. Developing effective methods to change these drinking behaviours could inform policies to improve population health. In line with an increasing interest in environmental-level interventions – i.e., changing the environment in which a behaviour occurs in order to change the behaviour of interest – this review first describes the existing evidence of the impact of glassware design (including capacity and shape) on drinking behaviours (e.g., at the 'micro' level – including sip size, as well as at the macro level – including amount consumed). The roles of two sets of possible underlying mechanisms – perception and affordance – are also explored. Finally, this review sets out a provisional typology of drinking behaviours to enable more systematic approaches to the study of these behaviours. While there is a paucity of evidence – in particular on measures of consumption – this growing evidence base suggests promising targets for novel interventions involving glassware design to reduce the consumption of drinks that harm health. Trial registration: ISRCTN.org identifier: ISRCTN10456720.